ChemInform Abstract: Fast Synthesis of K0.5Na0.5NbO3 Powders at Low Temperatures by Microwave Hydrothermal Method. Issue 17 (April 2016) - Chen, Liangping; Qiu, Guibo; Peng, Ben; Guo, Min; Zhang, Mei
Abstract: Perfect cubic and well crystalline pure K0.5 Na0.5 NbO3 powders are prepared by microwave hydrothermal reaction of Nb2 O5 in 6 M NaOH/KOH (1:5) solution (autoclave, 170 °C, 2 h).